The Impact of Mobile SMS Advertisements on worker’s Attitudes: Empirical Study - Megdadi, Younes; Hammouri, Mohammad; A.al-sarayreh, Aktham (British Journal of Marketing Studies, 2019)
This study aims to examine the impact of mobile SMS advertisements on working people’s attitudes and buying decisions. A number of marketing contributions to marketing management to allocate sales opportunities for business firms products. Mobile SMS advertisements allows business firms to introduce its products directly to their potential customers and their attitudes for adopting their buying decisions toward the offering products. A number of sub variables concerning mobile SMS advertisements namely personal communication, personal privacy, personal social involvement, personal interests, and personal life style. Study sample consist of (500) working women's in both public and privet sectors in Jordan. The study results show that the personal life style, personal social involvement, and personal privacy are the most mobile SMS advertisements variables influencing workers’ attitudes.